Management of large pelagic fisheries in CARICOM countries - Mahon, Robin; McConney, Patrick; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2004)
Large pelagic fish are important to the small-scale, commercial and recreational fisheries in many Caribbean Community countries. As most are transboundary, their management requires collaboration among countries in the context of international fisheries agreements. The FAO Technical Cooperation Programme project described in this report sought to assist CARICOM countries in formulating an approach to the development and management of large pelagic fisheries. The project compiled and reviewed a wide range of material, including status of resources, fishery harvest and post-harvest sectors, status of national and regional management initiatives, and the extent to which countries are engaged in international management activities such as those undertaken by the International Commission for the Conservation of Atlantic Tunas (ICCAT)
Keywords: Fishery management; Fisheries